Public Policy Network Implementation: A Case Study in the Development Urban Farming for Sustainable Food Independence in Makassar City - Mahyudin, Mahyudin; Ibrahim , Muh. Akmal; Yunus , Muhammad; Syahribulan, Syahribulan; Iskandar, Didik (Journal of Management and Administration Provision, 2025)
Urban farming uses land intensification to meet the daily need for fresh fruit and vegetables for residential areas in urban areas. Urban agriculture provides positive value in meeting food needs and practical values ​​that are meaningful for environmental and regional economic sustainability. Urban farming solves the problems above by creating green open space through open land management amid dense buildings and urban settlements. This research aims to analyze the implementation of development network policies for urban farming for sustainable food independence in Makassar City. This research uses a descriptive qualitative approach with data collection methods, namely observation, in-depth interviews, and documentation. The informants in this research are the authorities and are directly involved in the development of urban farming for sustainable food independence in Makassar City. The research results show that the implementation of the development policy network urban farming for sustainable food independence in Makassar City, it still needs to be improved through joint actions carried out between stakeholder. This is because there is still a lack of instructors assisting the Women Farmers Group (KWT) which is the target of the program urban farming in Makassar City. So, this influences the sustainability of the activities of utilizing yard land into productive land which can help in food independence for the people of Makassar City.